2020
DOI: 10.3390/ani10091454
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Evaluation of the Mitral Valve in Cavalier King Charles Spaniels

Abstract: This prospective cross-sectional study aimed to: (1) characterize echocardiographic features of mitral valve in MMVD affected Cavalier King Charles Spaniels (CKCS), focusing on dogs classified as American College of Veterinary Internal Medicine (ACVIM) class B1; (2) compare echocardiographic data in ACVIM B1 dogs divided on the basis of age at time of MMVD diagnosis, in order to understand if different aged subjects had different echocardiographic patterns. Length (AMVL), width (AMVW) and area (AMVA) of the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
1
7
0
1
Order By: Relevance
“…On echocardiographic examination, MVP was a common finding in our population (88%). This result is in accordance with previous studies conducted on CKCSs [ 16 , 18 , 31 ]. Our results showed that the presence and the severity of MVP were independent of sex; on the contrary, MVP severity was significantly positively associated with age and negatively with BW.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…On echocardiographic examination, MVP was a common finding in our population (88%). This result is in accordance with previous studies conducted on CKCSs [ 16 , 18 , 31 ]. Our results showed that the presence and the severity of MVP were independent of sex; on the contrary, MVP severity was significantly positively associated with age and negatively with BW.…”
Section: Discussionsupporting
confidence: 94%
“…An interesting finding was that 16% of the 56 dogs with echocardiographic evidence of MMVD and without signs of cardiac remodelling did not present murmur on cardiac auscultation. This percentage is lower than that reported in a recent publication [ 31 ], but it should be taken into account when applying breed schemes based solely on auscultation [ 36 ].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The aim of this study was to investigate morphometric measurements in relation with echocardiographic features of MMVD in American College of Veterinary Internal Medicine (ACVIM) class B1 CKCS [14]. This class, in fact, includes the majority of the breeding population and is very heterogeneous from clinical, morphological and echocardiographic points of view [15].…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted April 15, 2021. ; https://doi.org/10.1101/2021.04. 15.439951 doi: bioRxiv preprint 4 (ACVIM) class B1 CKCS [14]. This class, in fact, includes the majority of the breeding population and is very heterogeneous from clinical, morphological and echocardiographic points of view [15].…”
Section: Introductionmentioning
confidence: 99%